Influence of oxygen adsorption and diffusion on the overlapping of intergranular potential barriers in SnO2 thick films - Ponce, Miguel Adolfo (2004)
Complex impedance analysis and transient response studies in SnO2 thick films show the impedance dependence on gaseous environment and temperature. Possible mechanisms responsible for the found behaviors are proposed. The influence of temperature on the oxygen diffusion into the grains annihilating oxygen vacancies was detected. In particular, we found the transition from having bulk regions unaffected by surface phenomena to the overlapping of potential barriers due to an oxidizing gas.